POSSIBLE SOLUTIONS FOR PREVIOUS LIVANU BIOCHEMICAL FACTORY TERRITORY RECONSTRUCTION - Luksta, Ilze; Matisovs, Ivars (HUMAN. ENVIRONMENT. TECHNOLOGY. Proceedings of the Students International Scientific and Practical Conference, 2018)
This article summarizes and analyzes the available information about previous Livanu Biochemical factory current situation and offer opportunity for reconstruction solutions. On-site done therritorial condition determation- air and soil quality testing. Based on gained information, developed three possibilities about therritorial reconstruction solutions.